PENYULUHAN MITIGASI BENCANA PADA REMAJA TERHADAP POTENSI KEBAKARAN DI LINGKUNGAN GAPUK UTARA - Baiq Nurainun Apriani Idris; Irwan Hadi, Supriyadi, Baiq Nurul Hidayati (JOURNAL OF COMMUNITY DEDICATION, 2022)
Disasters caused by nature and human negligence both cause harm to the environment and the economy. Fire is one of the disasters with real losses. Adolescence is a physical dimension with high potential, especially rapid achievement of thinking skills and shifting about new roles in society. Increasing the knowledge and abilities of adolescents by conducting simulations will increase their awareness and ability to deal with fires. From the results of the pre-test and post-test given during the extension activities, from the results of the pre- test there were 8 people in the sufficient category and 10 in the poor category and during the post-test there were 12 people in the good category and 6 people in the sufficient category.